Gender, Politics, and Digital Media: OSINT´s method insights from the 2024 European Elections in Portugal - Oliveira, H.; Álvares, Cláudia (Congreso "Teorías de la comunicación y estudios de género: una simbiosis necesaria". II Congreso Nacional de la sección Género y Comunicación. VIII Congreso Nacional de_la sección Teorias y Métodos de Investigación en Comunicación. Universidad de Málaga, España, 2025)
This research observes how gender-related themes were addressed in the digital political campaigns of Chega (far-right) and Bloco de Esquerda (far-left) during the 2024 European Elections in Portugal. The study advances methodologically by adopting Open-Source Intelligence (OSINT) techniques for qualitative digital data analysis, moving beyond conventional content analysis approaches. OSINT enables a systematic mapping of discursive dynamics and political engagement strategies based on public and legally accessible online sources. Data collection was carried out across digital platforms such as Google Search, YouTube, Instagram, and TikTok. The objective was to identify dissemination patterns, audience interaction, and networks that amplify political discourse. This methodological approach not only enhances the understanding of contemporary political communication but also provides insights into symbolic disputes surrounding gender issues in a context marked by growing digital polarization. The findings reveal stark contrasts between the discursive strategies of the two parties. Bloco de Esquerda emphasizes values such as diversity, empowerment, and inclusive policies, using humor as a critical tool to challenge patriarchal norms and promote a progressive agenda. In contrast, Chega reinforces traditional gender roles and resorts to emotional appeals rooted in nostalgia, conservative morality, and resistance to sociocultural change. Humor in Chega’s communication is employed sarcastically to delegitimize ideological opponents and reinforce anti-gender narratives. The originality of this research lies not only in the choice of the object of study—the intersection of gender, politics, and digital communication—but also in the application of OSINT techniques within the field of Communication Sciences. Although widely used in cybersecurity and investigative journalism, OSINT remains underexplored in Portuguese communication research. This gap presents an opportunity to investigate the analytical potential of these tools for forensic and discursive analysis of highly dynamic and politicized digital environments. By integrating gender studies with innovative digital research methods, this study contributes to both theoretical and empirical advancements in understanding contemporary media strategies. It offers new perspectives for critical investigations into electoral campaigns, anti-gender narratives, and emerging forms of political engagement on social media. Furthermore, it underscores the importance of a symbiotic relationship between communication theory and gender studies as essential for grasping the communicational and democratic challenges facing Europe today.